2006
DOI: 10.1093/eurheartj/ehi749
|View full text |Cite
|
Sign up to set email alerts
|

Coronary endothelial dysfunction is associated with erectile dysfunction and elevated asymmetric dimethylarginine in patients with early atherosclerosis

Abstract: CED is independently associated with ED and plasma ADMA concentration in men with early coronary atherosclerosis. This study further supports the role of the endothelium in systemic vascular diseases and the role of ADMA in the systemic manifestations of endothelial dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(64 citation statements)
references
References 46 publications
3
61
0
Order By: Relevance
“…Previous studies demonstrated the relationship between plasma ADMA levels and the degree of endothelial dysfunction of forearm vascular beds in patients who were undergoing maintenance hemodialysis (30) and in hypertensive patients (31). Furthermore, coronary endothelial dysfunction is independently associated with the plasma ADMA concentration in men with early coronary atherosclerosis (32). Although reduced renal function is associated with attenuated coronary vasodilator capacity in patients with nonobstructive coronary artery disease (33), no investigation has examined the endothelial function of the coronary artery in CKD.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated the relationship between plasma ADMA levels and the degree of endothelial dysfunction of forearm vascular beds in patients who were undergoing maintenance hemodialysis (30) and in hypertensive patients (31). Furthermore, coronary endothelial dysfunction is independently associated with the plasma ADMA concentration in men with early coronary atherosclerosis (32). Although reduced renal function is associated with attenuated coronary vasodilator capacity in patients with nonobstructive coronary artery disease (33), no investigation has examined the endothelial function of the coronary artery in CKD.…”
Section: Discussionmentioning
confidence: 99%
“…In various pathological states, such as hypercholesterolaemia, hyperglycaemia, hyperhomocysteinaemia, HTA and CAD, plasma levels of ADMA may be increased and lead to inhibition of NO synthesis and endothelial dysfunction Elesber et al (2006), Wierzbicki et al (2006). Thus, ADMA could be used as a biochemical indicator of endothelial dysfunction, as it seems to be responsible for the pathophysiological link between this condition and ED Wierzbicki et al (2006).…”
Section: Discussionmentioning
confidence: 99%
“…Since the publication of the algorithm in 2005, additional research studies have further supported the advisory panel recommendations. 6 Primary care physicians should be the key clinicians to screen for ED. This study is an observational study with a small sample size; for that reason, further multi-centre studies are recommended to stress on the following questions: Should an enquiry about sexual health, as a reflection of vascular health, be part of routine physicals for young men?…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a paucity of information regarding the prevalence and relationship between ED and early coronary atherosclerosis. 6 The presence of ED should prompt an aggressive assessment of occult vascular disease; many men with erectile difficulty would benefit from an early, aggressive management of cardiovascular risk factors, with both lifestyle modifications and pharmacotherapy to achieve optimal target goals under existing treatment guidelines. 7,8 The aim of this study was to determine the cardiovascular risk factors among men with ED attending a hospitalbased primary care clinic in Riyadh, Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%